2017
DOI: 10.1158/1078-0432.ccr-17-0675
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Whole Genome Sequencing on Circulating Cell-Free DNA Allows Reliable Noninvasive Copy-Number Profiling in Neuroblastoma Patients

Abstract: Neuroblastoma (NB) is a heterogeneous disease characterized by distinct clinical features and by the presence of typical copy-number alterations (CNAs). Given the strong association of these CNA profiles with prognosis, analysis of the CNA profile at diagnosis is mandatory. Therefore, we tested whether the analysis of circulating cell-free DNA (cfDNA) present in plasma samples of patients with NB could offer a valuable alternative to primary tumor DNA for CNA profiling. In 37 patients with NB, cfDNA analysis u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 54 publications
(69 reference statements)
4
99
0
Order By: Relevance
“…This study revealed chromosome arm gains and losses, high level copy number gains, fusions and SNVs indicated in the pathogenesis of prostate cancer, therefore the timely and costly deep coverage WGS may be avoidable. Finally, the use of either the same analysis platform for both cfDNA and tumour or analysing all samples on both platforms may reduce the discordance rates attributed to differences in sensitivity [55].…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed chromosome arm gains and losses, high level copy number gains, fusions and SNVs indicated in the pathogenesis of prostate cancer, therefore the timely and costly deep coverage WGS may be avoidable. Finally, the use of either the same analysis platform for both cfDNA and tumour or analysing all samples on both platforms may reduce the discordance rates attributed to differences in sensitivity [55].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Figure 1 shows processing of cfDNA and primary and metastatic tumour tissue from sampling to analysis and the summary of contributing factors to discordance rates observed between SGAs in cfDNA and tumour tissue. A range of SGAs including numerical chromosome alterations (NCAs), segmental chromosome alterations (SCAs) and large SCAs have been investigated in cfDNA in neuroblastoma patients [53][54][55]. Chicard et al, inferred CNAs (including large SCAs, SCAs and NCAs) in cfDNA and matched tumour tissue of neuroblastoma patients.…”
Section: The Underlying Factors Contributing To Perceived Discordancementioning
confidence: 99%
“…Especially, ultradeep duplex sequencing for mutation calling appears to be a promising approach; however, it remains expensive, requires targeted panels, and is yet to be extensively validated for its clinical use [10]. Shallow (coverage 0.1-0.5×) whole-genome sequencing (sWGS), on the other hand, has been shown to reliably detect copy number alterations (CNAs) in cfDNA [11][12][13]. As for single nucleotide polymorphisms (SNPs), specific CNAs are widely described to correlate with diagnosis in lung cancer [14].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Other efforts exploring cell-free DNA in pediatric cancer have focused on detection of copy number aberrations, structural variants 32,33 and mutations 34 . However, these alterations come with low specificity for classification of pediatric solid tumors according to their histopathological diagnosis 35 .…”
Section: Discussionmentioning
confidence: 99%